Pengaruh Metode Talking Stick terhadap Hasil Belajar Siswa pada Mata Pelajaran Sejarah Indonesia Kelas X SMA Negeri 5 Kota Serang - Rully Aprilia (LPPM Institut Nasional Laa Roiba Bogor, 2023)
Obstacles in the history learning process in class X IPS 3 SMA Negeri 5 Kota Serang are due to the use of conventional methods used by teachers, so students are not actively involved. The formulation of the problem in this study is whether the Talking Stick method can improve student learning outcomes in Indonesian history subjects in class X IPS 3 SMA Negeri 5 Kota Serang?. The purpose of this study was to improve student learning outcomes after applying the Talking Stick method to the History subject of Class X IPS 3 at SMA Negeri 5 Kota Serang. This type of research is Classroom Action Research (CAR), in this study there were three cycles, namely Pre-Cycle, Cycle I and Cycle II. The data collection in this study was a test of learning outcomes and observation sheets. Based on the results obtained, there was an increase in student learning outcomes after the implementation of this method. In this class there were 48 students with 14 girls and 14 boys. In this study the researchers only involved a sample of 30 students consisting of 15 male students and 15 female students. This can be seen from the increase in student learning outcomes in cycle I of 65.1 and cycle II of 72.8. So it can be concluded that using the Talking stick method can improve student learning outcomes in Indonesian History subjects and is able to increase students' interest in learning in the implementation of Indonesian History learning. Keywords: Talking stick; Learning Outcomes; Indonesian History.